In Vitro Control of Pathogenic Fungi Associated with Selected Brri Rice Varieties (Bioresearch Communications, 2023)
The present study evaluated the efficacy of five chemical fungicides, viz., Capvit 50 WP, Cynil 72 WP, Kochi 80 WDG, Sinozim 50 WP and Ridomil Gold MZ 68 WG along with five plant extracts, specifically Azadirachta indica A. Juss., Adhatoda vasica Nees., Psidium guajava L., Cassia alata L. and Citrus limon on the radial mycelial growth of two pathogenic fungi, Curvularia lunata and Drechslera oryzae associated with newly released BRRI rice varieties at varying concentrations. Capvit 50 WP exhibited complete inhibition of C. lunata at 300, 400 and 500 ppm concentrations as well as D. oryzae at 200, 300, 400 and 500 ppm concentrations leading the selected fungicides, followed by Cynil 72 WP and Ridomil Gold MZ 68 WG. Out of the five plant extracts, P. guajava demonstrated maximum radial growth inhibition (72.2%) against C. lunata at 20% concentration followed by A. indica. (56%), A. vasica. (52.3%), C. alata (24%) and C. limon (18.1%). Capvit 50 WP and Cynil 72 WP, among the fungicides, are potential in vivo controls for the tested pathogens associated with rice varieties. Additionally, out of the five plant extracts, Psidium guajava L. can be effective against C. lunata, while Azadirachta indica A. Juss. is a promising botanical fungicide against D. oryzae.Bioresearch Commu. 10(1): 1393-1397, 2024 (January)